Analysis Of Violations Of School Rules In Upper Grade Students At MIN 4 Jember - Efendi, Erfan; Ramadhan, Firman Aulia; Ubaidillah, Sofwan Roif (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to determine the types, causes and efforts of school rule violations. The research approach uses qualitative and descriptive research adopting the Miles & Huberman model which includes data reduction, data presentation, and conclusions. Data were collected through documentation, observation, and interviews. The research subjects were 14 people, consisting of 3 class teachers and 11 students in grades IV, V, and VI. The results showed that the forms of rule violations include not arriving on time, wearing uniforms that are not in accordance with school regulations, not practicing school hygiene, students' hair being colored and long, not following class picket duties, not submitting assignments on time, and being disrespectful. The causes that influence students to violate school rules are students who are slow in accepting learning and following the wrong peers. This can be overcome by conveying information about the importance of student compliance with school regulations and incidental checks. In addition, providing severe punishment for violators, increasing cooperation between the Principal and homeroom teachers, and increasing individual supervision (strict supervision/control).